A Study of Organizational Quality Climate in Public Sector - Salmiah, Mohd. Ali (1994)
This study was carried out to look at the concept of “Quality First” in the Service organisations in the public sector. For this study, the analysis was done on the dimensions and the factors that influence the organisation’s quality climate. Analysis of the assessment of the climatic factors such as Strategic Focus, Leadership and Management, Work Force, Customer-orientation, and Communication in organisations required the sending out of questionnaires to 97 government organisations in Alor Setar, Kedah Darul Aman. The score of 5.039 was obtained in this study which exceeded the target score of 3.5. This indicates that the organisation climate in the government sector is favourable and conducive for quality improvement effort. The survey showed that managers in the public sector are committed to the quality improvement that the government emphasised upon. Analysis of the factors that influenced the organisation climate shows that there is no significant difference to the size of the work force, size if its budget, the level of government, its function or mission, past performance of total quality effort, and the perception of managers regarding their organisation’s performance. This shows that the organisations in the public sector are the same since they are required to follow the guidelines that the government has put forward in the various circulars pertaining to the quality improvement and implementation. Thus, it can be concluded that public agencies in the govermnent have favourable quality climate which is suitable for any total quality improvement effort required by the government. However, the agencies should nor rest on their laurels but still need to strive for continuous improvement in its total quality effort to achieve the country’s vision 2020.